The Effects of Pharmacological Inhibition of Histone Deacetylase 3 (HDAC3) in Huntington’s Disease Mice - Jia, Haiqun (PLoS One, 2016)
An important epigenetic modification in Huntington’s disease (HD) research is histone acetylation, which is regulated by histone acetyltransferase and histone deacetylase (HDAC) enzymes. HDAC inhibitors have proven effective in HD model systems, and recent work is now focused on functional dissection of the individual HDAC enzymes in these effects. Histone deacetylase 3 (HDAC3), a member of the class I subfamily of HDACs, has previously been implicated in neuronal toxicity and huntingtin-induced cell death. Hence, we tested the effects of RGFP966 ((E)-N-(2-amino-4-fluorophenyl)-3-(1-cinnamyl-1H-pyrazol-4-yl)acrylamide), a benzamide-type HDAC inhibitor that selectively targets HDAC3, in the N171-82Q transgenic mouse model of HD. We found that RGFP966 at doses of 10 and 25 mg/kg improves motor deficits on rotarod and in open field exploration, accompanied by neuroprotective effects on striatal volume. In light of previous studies implicating HDAC3 in immune function, we measured gene expression changes for 84 immune-related genes elicited by RGFP966 using quantitative PCR arrays. RGFP966 treatment did not cause widespread changes in cytokine/chemokine gene expression patterns, but did significantly alter the striatal expression of macrophage migration inhibitory factor (Mif), a hormone immune modulator associated with glial cell activation, in N171-82Q transgenic mice, but not WT mice. Accordingly, RGFP966-treated mice showed decreased glial fibrillary acidic protein (GFAP) immunoreactivity, a marker of astrocyte activation, in the striatum of N171-82Q transgenic mice compared to vehicle-treated mice. These findings suggest that the beneficial actions of HDAC3 inhibition could be related, in part, with lowered Mif levels and its associated downstream effects.